Pengaruh Kecerdasan Emosionalterhadap Kesantunan Berbahasa Dan Kesantunan Berperilaku Siswa Kelas V - Dewi Khalishah; Lukman Hakim (Institut Agama Islam Negeri Ponorogo, 2025)
Emotional intelligence is the ability to motivate and manage emotions. Meanwhile, polite language and behavior are important aspects in building harmonious relationships between individuals, especially in social environments.This research aims to determine and describe (1) whether or not there is an influence of emotional intelligence on politeness in language of class V students at MI Ma'arif Setono, (2) whether or not there is an influence of emotional intelligence on politeness in behavior of class V students at MI Ma'arif Setono. This research uses a quantitative approach in the form of ex post facto. The data collection technique used is the saturated sampling technique. The data analysis technique used is simple linear regression. Based on the results of research and data analysis, it can be seen that (1) there is a significant influence between emotional intelligence on language politeness of class V students at MI Ma'arif Setono for the 2023/2024 academic year, proven based on the value of Fcount (13.227) > Ftable (3, 47), with the regression equation Y1 = 15.464 + 0.745 X, so that H01 is rejected and Ha1 is accepted, with an influence of 37.5%, (2) there is a significant influence between emotional intelligence on polite behavior in class V at MI Ma'arif Setono for the 2023/2024 academic year, proven by the value of Fcount (28.175) > Ftable (3.47), with the regression equation Y2 = 11.174 + 0.628 X, so H02 rejected and Ha2 accepted, with an influence of 56.2%.